Caspase-3 apoptotic induction by Iraqi Newcastle disease virus on mammary adenocarcinoma transplanted in mice - Al-Shammari, Ahmed Majeed (Iraqi Journal of Cancer and Medical Genetics, 2014)
This study aimed to investigate the ability of Iraqi strain of Newcastle Disease Virus (NDV) to induce apoptosisin vivothrough Caspase 3 activation when administered intratumoral and compared to intra-peritoneal injection.Immunohistochemistry test was used for detecting apoptosis by using mAb against Caspase-3. Histopathological sections for the treated tumor mass showed proliferation of granulation tissue with extensive area of necrosis (mixture of apoptotic and necrotic cells).This revealed that NDV infection induce apoptosis significantly in mammary adenocarcinoma (AM3) when compared to control group proved by high expression of caspase-3.In vivo immunohistochemical detection of Caspase 3in mammaryadenocarcinoma which give brown stain revealed a significantly(p<0.05)increase in the mean percentage of cells expressing caspase 3 in NDV treated group compared with low increase in the mean percentage of cells expressing caspase 3 in untreated control group at day 1,2,3,7, and at 14 day. These results revealed that NDV had powerful effect on inducing apoptosis in mammary adenocarcinoma (AM3) during its replication inside the tumor mass for long time after one single injection. This study indicate the role of NDV Iraqi strain in inducing apoptosis as confirmed by caspase-3 activation in cancer cells which is interesting confirmed feature that make NDV Iraqi strain as anti-tumor agnet.